The master of secrets - Lliteras, D. S. (Charlottesville, VA : Hampton Roads Pub., 2007)
"D. S. Lliteras's latest novel follows Addan, a young boy searching for his father, a disciple of Jesus. Along the way, Addan encounters bandits, lepers, and con men before teaming up with Jeshua, an entertainer and opportunist, who protects the boy while at the same time using him to help swindle unsuspecting strangers"--Provided by publisher.
Keywords: Jesus Christ -- Fiction; Orphans -- Fiction; Swindlers and swindling -- Fiction; Apostles -- Fiction; Christian fiction